2017
DOI: 10.3844/ojbsci.2017.251.259
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Leaf Characteristics with Tree Age in <i>Dryobalanops beccarii</i> Dyer in a Restored Forest of Sarawak, Malaysia

Abstract: Study on leaf properties of an endangered dipterocarp tree species, Dryobalanops beccarii, was conducted in a restored forest. The study focused on the morphology, nutrient concentration and gas exchange in well-developed leaves of D. beccarii at different ontogenetic phases. The hypothesis tested that leaf physiological and morphological changes are related to the nutrient concentration level of D. beccarii leaves in each ontogenetic phase. Seedling leaves were small and thin, whereas adult tree leaves were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Some studies show how traits may differ with plant age-size (Gibert et al 2016). Other studies have found variation in functional leaf traits at different ontogenetic phases in the restoration context (e.g., , Lapok et al 2017.…”
mentioning
confidence: 99%
“…Some studies show how traits may differ with plant age-size (Gibert et al 2016). Other studies have found variation in functional leaf traits at different ontogenetic phases in the restoration context (e.g., , Lapok et al 2017.…”
mentioning
confidence: 99%